Weimar - Unknown:::Creator::::::::::::; Meyer, Joseph, 1796-1856 (author):::Contributor:::::::::::: (Kunstanst d. Bibliographisches Institut; Germany; Hildburghausen)
Engraving with a panoramic view from the countryside of Weimar, Germany